2015
DOI: 10.2134/jeq2014.01.0036
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Socio-Bio-Geo-Chemistry and Engineering of Nitrogen Management in Two Illinois Tile-Drained Watersheds

Abstract: Reducing nitrate loads from corn and soybean, tile-drained, agricultural production systems in the Upper Mississippi River basin is a major challenge that has not been met. We evaluated a range of possible management practices from biophysical and social science perspectives that could reduce nitrate losses from tile-drained fields in the Upper Salt Fork and Embarras River watersheds of east-central Illinois. Long-term water quality monitoring on these watersheds showed that nitrate losses averaged 30.6 and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…fields in the upper Midwest of the United States is a well-established environmental issue (e.g., David et al, 2010). Many in-field and edge-of-field techniques have been proposed and evaluated for reducing these nitrate losses, including fertilizer management, cover crops, perennial crops, water table management, constructed wetlands, buffer strips, two-stage ditches, saturated buffers, and bioreactors (e.g., USEPA, 2008;Schipper et al, 2010b;Skaggs et al, 2012;Jaynes and Isenhart, 2014;David et al, 2015;Groh et al, 2015). The effectiveness of these practices is variable from location to location and temporally due to differing tile flow amounts and nitrate concentrations.…”
Section: Temperature and Substrate Control Woodchip Bioreactor Performentioning
confidence: 99%
See 3 more Smart Citations
“…fields in the upper Midwest of the United States is a well-established environmental issue (e.g., David et al, 2010). Many in-field and edge-of-field techniques have been proposed and evaluated for reducing these nitrate losses, including fertilizer management, cover crops, perennial crops, water table management, constructed wetlands, buffer strips, two-stage ditches, saturated buffers, and bioreactors (e.g., USEPA, 2008;Schipper et al, 2010b;Skaggs et al, 2012;Jaynes and Isenhart, 2014;David et al, 2015;Groh et al, 2015). The effectiveness of these practices is variable from location to location and temporally due to differing tile flow amounts and nitrate concentrations.…”
Section: Temperature and Substrate Control Woodchip Bioreactor Performentioning
confidence: 99%
“…We installed two bioreactors in the Embarras River watershed in east-central Illinois, the site of extensive previous work on tile drainage and nitrate loss (e.g., David et al, 1997David et al, , 2015Gentry et al, 2014). The watershed has extensive poorly and very poorly drained Mollisols that are typically tile drained and would be an excellent candidate for using wood chip bioreactors to reduce riverine nitrate loads that average 30 kg N ha −1 yr −1 (Gentry et al, 2014).…”
Section: Study Site and Bioreactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing data from the USDA Agricultural Resource Management Survey (ARMS) of corn growers, Weber and McCann (2015) reported that of the 1840 observations, 27 % of the farmers in the study received their application recommendations from a fertilizer retailer, whereas 50 % said they did not receive any recommendations from anyone. In a survey of Illinois farmers, David et al (2015) found that out of pocket expenses were quoted as being the greatest factor that limited farmers' ability and willingness to implement water quality nutrient management, followed closely by lack of government funds for cost sharing and concerns about reduced yields. They indicated that financial incentives and more readily available evidence to demonstrate effective local pollution reduction would have the greatest effect on adoption rates.…”
Section: Socio-economic Impediments To Adopting the 4rsmentioning
confidence: 99%